The Effect of Phytonutrients in Terminalia chebula Retz. on Rumen Fermentation Efficiency, Nitrogen Utilization, and Protozoal Population in Goats - Pongsatorn Gunun; Anusorn Cherdthong; Pichad Khejornsart; Metha Wanapat; Sineenart Polyorach; Sungchhang Kang; Walailuck Kaewwongsa; Nirawan Gunun (Animals, 2022)
The aim of this study was to investigate the effect of Terminalia chebula meal (TCM) supplementation on digestibility, rumen fermentation, nitrogen utilization, and protozoal population in goats. Eight goats with an initial body weight (BW) of 13 ± 3.0 kg were randomly assigned according to a double 4 × 4 Latin square design to receive different levels of TCM supplementation at 0, 8, 16, and 24 g/kg of total dry matter (DM) intake, respectively. The goats were fed with concentrate diets at 13 g/kg BW, while rice straw was used as a roughage source, fed ad libitum. The results revealed that the feed intake and the apparent digestibility of DM, organic matter (OM), neutral detergent fiber (NDF), and acid detergent fiber (ADF) were similar among the treatments (p > 0.05). However, crude protein (CP) digestibility decreased significantly (p < 0.05) when supplemented with TCM at 24 g/kg of total DM intake (p < 0.05). The addition of TCM did not change the ruminal pH and blood urea nitrogen concentrations (p > 0.05), whereas the concentration of NH3-N at 4 h post feeding was reduced with the inclusion of TCM at 16 and 24 g/kg of total DM intake. The total numbers of bacteria were enhanced by the addition of TCM, while the protozoal population, in both entodiniomorph and holotrich, was reduced (p < 0.05). The supplementation of TCM did not change the concentration of total volatile fatty acids (TVFA), acetic acid, or butyric acid, while the propionic acid concentration at 4-h post feeding increased significantly, especially when supplemented at 16 g/kg of total DM intake (p < 0.05. In addition, urinary nitrogen (N) excretion decreased, while fecal N excretion, N absorption, N retention, and the proportion of N retention to N intake increased with the inclusion of TCM at all levels. In summary, the inclusion of TCM could improve rumen fermentation efficiency and N balance without having an adverse effect on feed intake, nutrient digestibility, and rumen ecology; however, the protozoal population decreased. Therefore, this study suggests that TCM (16 g/kg of total DM intake) could be used as a plant source for rumen enhancement in goats fed a diet based on rice straw without having an adverse effect on feed intake or nutrient digestion. However, further studies on the production of types of meat and milk that have a long-term feeding trial should be carried out.